Green adeptness in synthesis of non-toxic copper and cobalt oxide nanocomposites with multifaceted bioactivities - Mane, Pramod C.; Kadam, Deepali D.; Khadse, Ashok N.; Chaudhari, Aditya R.; Ughade, Supriya P.; Agawane, Sachin B.; Chaudhari, Ravindra D. (Cancer Nanotechnology, 2023)
Background: In the present era, we are facing different health problems mainly concerning with drug resistance in microorganisms as well as in cancer cells. In addition, we are also facing the problems of controlling oxidative stress and insect originated diseases like dengue, malaria, chikungunya, etc. originated from mosquitoes. In this investigation, we unfurled the potential of Achatina fulica mucus in green synthesis of mucus mediated copper oxide bio-nanocomposites (SM-CuONC) and cobalt oxide bio-nanocomposites (SM-Co3O4NC). Herein we carried out the physico-chemical characterization like UV-Vis spectra, X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Transmission electron microscopy (TEM), Energy Dispersive X-ray Analysis (EDAX) and X-ray photoelectron spectroscopy (XPS) of as synthesized bio-nanocomposites. Both the bio-nanocomposites were tested for their potential as antimicrobial activity using well diffusion assay, anticancer activity by MTT assay, antioxidant activity by phosphomolybdenum assay and mosquito larvicidal activity.Results: The results of this study revealed that, SM-CuONC and SM-Co3O4NC were synthesized successfully using A. fulica mucus. The FESEM and TEM data reveal the formation of nanoparticles with quasi-spherical morphology and average particle size of similar to 18 nm for both nanocomposites. The EDAX peak confirms the presence of elemental copper and cobalt in the analyzed samples. The X-ray diffraction analysis confirmed the crystalline nature of the CuO and Co3O4. The result of anti microbial study exhibited that, SM-CuONC showed maximum antimicrobial activity against Escherichia coli NCIM 2065 and Aspergillus fumigatus NCIM 902 which were noted as 2.36 +/- 0.31 and 2.36 +/- 0.59 cm resp. at 60 mu g/well concentration. The result of anticancer activity for SM-CuONC was exhibited as, 68.66 +/- 3.72, 62.66 +/- 3.61 and 71.00 +/- 2.36 percent kill, while SM-Co3O4NC exhibited 61.00 +/- 3.57, 72.66 +/- 4.50 and 71.66 +/- 4.22 percent kill against Human colon cancer (HCT-15), Cervical cancer (HeLa), and Breast cancer (MDA-MB-231) cell lines, respectively, at 20 mu g/well concentration. Both the nanocomposites also exhibited better antioxidant activity. Total antioxidant activity for SM-CuONC at 50 mu g/ml concentration was found to be highest as 55.33 +/- 3.72 while that of SM-Co(3)O(4)Ns was 52.00 +/- 3.22 mM of ascorbic acid/mu g respectively. Both bio-nanocomposites also exhibited 100% mosquito larvicidal activity at concentration ranging from 40 to 50 mg/l. During cytotoxicity study it is noted that at 5 mu g/well concentration, SM-CuO and SM-Co3O4NCs suspension showed more than 97% viability of normal (L929) cell lines. We also studied phytotoxicity of both bio-nanocomposites on Triticum aestivum. In this study, 100% seed germination was observed when seeds are treated with SM-CuONC and SM-Co3O4NC at 500 mg/l and 250 mg/l concentration respectively.Conclusions: This study concludes that in future as synthesized SM-CuONC and SM-Co3O4NC can be used in pharmaceutical, health care system for betterment and welfare of human life as both bio-nanocomposites exhibits better antimicrobial, anticancer, antioxidant and mosquito larvicidal potential.
Keywords: Achatina fulica mucus; Bio-nanocomposites; Biological activities; Characterization; Toxicity

Green synthesis of silver and gold ultra nanocomposites from silk fibroin and their application for treatment of endodontic infections - Pramod C.; Pawar, Jayant; Mane, Deepali P.; Khadase, Ashok N.; Chaudhari, Aditya R.; Ughade, Supriya P.; Chaudhari, Ravindra D.; Agawane, Sachin B. (Emergent Materials, 2024)
The present study is designed to investigate the antibacterial efficacy of B. mori silk fibroin based silver and gold ultra bio-nanocomposites (SF-AgUNC and SF-AuUNC) against Enterococcus faecalis for endodontic disinfection. The SF-AgUNC and SF-AuUNC based irrigant solution was tested in- vitro against Enterococcus faecalis (ATCC: 29212). In this direction, SF-AgUNC and SF-AuUNC synthesized by silk fibroin are very important as they are economically cheap and easy to biosynthesize. The synthesis of SF-AgUNC and SF-AuUNC was accomplished by dissolving 1 mM silver nitrate and 0.5 mM auric chloride respectively in 10 ml of fibroin as precursors. The structural and morphological analysis was executed by UV-Vis Spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopic analysis (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Transmission electron microscopy (TEM), Energy-dispersive X-ray spectroscopy (EDAX) and X-ray photoelectron spectroscopy (XPS). The qualitative antimicrobial activity of SF-AgUNC and SF-AuUNC were performed against inoculum of Enterococcus faecalis containing 1⨯105 CFU/ ml. The same solutions were tested on dentine specimens inoculated with bacterial cultures and found remarkable biofilm reduction. The structural and morphological analysis reveals the formation of SF-AgUNC and SF-AuUNC having quasi-spherical morphology. The average particle size for SF-AgUNC and SF-AuUNC was same (~ 8 nm). The XRD study confirms that, both SF-AgUNC and SF-AuUNC were crystalline in nature. The bacterial growth inhibition and significant biofilm reduction was observed on dentine specimens treated with SF-AgUNC, SF-AuUNC and positive control. In antibacterial study, at 30 μg/well concentration of SF-AgUNC and SF-AuUNC, 3.13 ± 0.22 and 1.13 ± 0.22 cm of zone of inhibition was noted respectively. Moreover, growth of Enterococcus faecalis was completely inhibited at 20 μg/ml and 30 μg/ml when treated with SF-AgUNC and SF-AuUNC respectively. Hence, the present study concludes that SF-AgUNC and SF-AuUNC can be used as an effective intracanal medicament for the treatment of dental problems with no cyto toxicity.